Doping the Buckminsterfullerene by Substitution: Density Functional Theory Studies of C59X (X = B, N, Al, Si, P, Ga, Ge, and As) - Hongcun Bai; Wenxin Ji; Xiangyu Liu; Liqiong Wang; Nini Yuan; Yongqiang Ji (Journal of Chemistry)
The heterofullerenes C59X (X = B, N, Al, Si, P, Ga, Ge, and As) were investigated by quantum chemistry calculations based on density functional theory. These hybrid cages can be seen as doping the buckminsterfullerene by heteroatom substitution. The geometrical structures, relative stabilities, electronic properties, vibrational frequencies, dielectric constants, and aromaticities of the doped cages were studied systemically and compared with those of the pristine C60 cage. It is found that the doped cages with different heteroatoms exhibit various electronic, vibrational, and aromatic properties. These results imply the possibility to modulate the physical properties of these fullerene-based materials by tuning substitution elements.